Income, Lifestyle, and Personal Financial Management: The Mediating Role of Financial Literacy - Rizqi Amalliyah; Osly Usman (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This research looks at how income and lifestyle somehow shape personal financial management among active Master of Management students at Universitas Negeri Jakarta, and in the middle there is financial literacy as a cognitive mediator variable. A quantitative method was used, with an explanatory design, and the primary data came from 59 valid respondents, selected by purposive sampling, then it was analyzed using PLS SEM in SmartPLS. The empirical findings show that income gives a direct positive effect, and it is statistically significant too, on both financial literacy and personal financial management quality. Meanwhile, lifestyle choices do basically nothing, like fully neutral, they carry no statistically significant direct influence or indirect influence on either variable. This kind of structural neutrality implies that for these working postgraduate students, lifestyle stays as a sort of discretionary action, separated from the core routine of budgeting discipline. Also, financial literacy is shown to be the most critical foundational determinant, directly strengthening financial management. Lastly, the mediation analysis confirms that financial literacy works as a partial mediator for income but it does not mediate lifestyle, because lifestyle is statistically independent.